Intravenous infusion of salbutamol in the treatment of asthma. - Spiro, S G (1975)
The effects of i.v. infusion of increasing rates of salbutamol for up to 4 h were documented in ten convalescent asthmatic patients. 2 The major bronchodilator effect was seen at 4.16 mug/minute. A small further improvement occurred at infusion rates up to 25.0 mug/min but was not significantly better than that seen at the lower infusion rate. 3 Cardiovascular effects were minimal after 60 min at the lower rate and even at 25.0 mug/min mean heart rate rose by only 17.1 beats/minute. All patients tolerated the 4 h infusion well. 4 It is concluded that i.v. infusion of salbutamol may be a useful addition to the treatment of the patient with a severe attack of asthma.